Zootechnic and economic indicators of termination in feedlot of different genetic groups of lambs - Felipe Queiroga Cartaxo; Wandrick Hauss de Sousa; Marcílio Fontes Cezar; João Paulo de Farias Ramos; Iara Tamires Rodrigues Cavalcante; Maria das Graças Gomes Cunha; Josimar Torres Gomes; Mauricio Luiz de Mello Vieira Leite (Acta Scientiarum. Animal Sciences, 2021)
The objective of this work was to evaluate the performance, carcass traits and economic indicators of Santa Inês lambs and their crossings finished in feedlot. Thirty whole lambs (10 Santa Inês, 10 ½ Dorper + ½ Santa Inês and 10 ¾ Dorper + ¼ Santa Inês) were used, with 115 days of age and initial live weight of 20.07 kg. The lambs were kept for 60 days receiving sorghum silage and concentrate, after which they were slaughtered. The ¾ Dorper + ¼ Santa Inês lambs and the ½ Dorper + ½ Santa Inês lambs showed higher of dry matter intake and water intake, greater daily weight gain and body score in relation to Santa Inês lambs. The carcasses of ¾ Dorper + ¼ Santa Inês lambs showed better conformation, finishing and marbling. The gross profit margin showed positive values for all genetic groups, covering the effective operating cost. Dorper crossbred lambs had a higher gross margin compared to Santa Inês lambs. The cost of the diet represented on average 61.35% of the price paid per kilo of sheep meat. In the sheep meat production system, the genetic group influences the zootechnical and economic indicators of finishing feedlot of lambs.